PENENTUAN PENAMPUNGAN KORBAN BANJIR BERBASIS SISTEM INFORMASI GEOGRAFIS - Ahmad Zulfikri; Nugroho Adhi Santoso; Rifki Dwi Kurniawan (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
Floods are an annual problem that occurs in several areas in Indonesia. Evacuation of flood victims is very necessary in order to minimize the number of victims who fall, therefore it is necessary to carry out flood victims' shelters. The purpose of this study is to determine the shelter for flood victims based on geographic information systems. The method used in this study refers to qualitative research with literature studies. The results obtained include determining two stages, namely analyzing the determination of the flood zone (analyzing the terrain map, Landsat imagery, rainfall data, and making river buffer maps) and analyzing the data (spatial and attribute analysis). The conclusion that can be drawn from this research is that placing flood victims shelters by utilizing Geographic Information Systems can be done with database development and data analysis, starting with analysis of flood zone determinants, and data analysis. The data becomes a reference to determine an effective direction on the flood disaster path in a certain area.